Rhetorical Moves and Research Gap Strategies of High-Reputable ELT Research Article Abstracts - Salsabila, Almeira; Jabu, Baso; Sahril, Sahril (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
The objectives of this research were: (1) to investigate rhetorical moves employed in high-reputable ELT research article abstracts; (2) to investigate research gap strategies employed in high-reputable ELT research article abstracts; (3) to explore how do authors establish rhetorical moves and research gap strategies using linguistic features in high-reputable ELT research article abstracts. This research involved mixed method analysis. The source of the data consisted of 100 research article abstracts published in high-reputable journals. The researcher applied Hyland’s (2000) framework for analyzing rhetorical moves and Arianto’s (2021) framework for analyzing research gap strategies. The researcher read and code each of the segments within the abstract that characterize each of the moves. The result of this research reveals that: (1) the most frequent move was product moves with the most frequent moves pattern I-P-M-Pr-C; (2) the most frequent research gap strategy was the strategy-2 (revealing limitation of the previous research); (3) the linguistic features addressed in rhetorical moves and research gap strategies were indicated by the using of discourse markers, phrases, and tenses emerged in every segment within the abstracts. The researcher found newly emerged form within the product moves, called as ‘evaluating findings’ which may be worth considering for the future studies. The researcher also suggests the future researchers to explore the study of centrality claims or any promotional techniques used by authors in promoting research articles through abstracts. Keywords: Abstracts, High-Reputable Journals, Rhetorical Moves, Research Gap Strategies